A New Cytogenetic Biodosimetry Image Repository for the Dicentric Assay. Issue 1 (23rd December 2016) - Romm, Horst; Beinke, Christina; Garcia, Omar; Di Giorgio, Marina; Gregoire, Eric; Livingston, Gordon; Lloyd, David C.; Martìnez-Lopez, Wilner; Moquet, Jayne E.; Sugarman, Stephen L.; Wilkins, Ruth C.; Ainsbury, Elizabeth A.
Abstract: The BioDoseNet was founded by the World Health Organization as a global network of biodosimetry laboratories for building biodosimetry laboratory capacities in countries. The newly established BioDoseNet image repository is a databank of 25 000 electronically captured images of metaphases from the dicentric assay, which have been previously analysed by international experts. The detailed scoring results and dose estimations have, in most cases, already been published. The compilation of these images into one image repository provides a valuable tool for training and research purposes in biological dosimetry. No special software is needed to view and score the image galleries. For those new to the dicentric assay, the BioDoseNet Image Repository provides an introduction to and training for the dicentric assay. It is an excellent instrument for intra-laboratory training purposes or inter-comparisons between laboratories, as recommended by the International Organization for Standardisation standards. In the event of a radiation accident, the repository can also increase the surge capacity and reduce the turnaround time for dose estimations. Finally, it provides a mechanism for the discussion of scoring discrepancies in difficult cases.